Creating Supply Chain Management Algorithm for University Integration in the National Innovation System - Gennady I. Lazarev; Svetlana Va. Krivoshapova; Vyacheslav G. Krivoshapov; Anatoliy N. Yarygin (International Journal of Supply Chain Management, 2018)
Abstract- The current development trend, ensuring the welfare of the state, is in constant connection with the activity of innovation. Under the influence of sophisticated and innovative processes, the concept of the national innovation system based on the macroeconomic level is steady in general. Numerous elements are seen in the conjugation of the national innovation system scale, among which higher education institutions and their scientific and innovative potential take their place. However, the reverse side is inequality in the levels of university integration, which introduces a discrepancy between the degree of their effectiveness as the elements of the national innovation system. So it becomes urgent to have a specific set of steps to improve the level of university integration. The process of integration level increase must be governed necessarily by the principles of suitable integration condition supply chain management, where it is possible to justify waiting by the creation of a supply chain management algorithm for university integration in the national innovation system. The result of such an algorithm application is the obtaining of a visual set of steps by a user to ensure the process of managerial decision making and implementation to improve the level of university integration in the national innovation system. The increase of university integration will directly enhance its interaction with other elements of NIS, and therefore will increase its contribution to the national economic development, and other priority areas of the state. Key Words- Innovation, National innovation system, University integration, Supply chain management, Decision-Making algorithm.